Meningkatkan atau Menghambat? Persepsi Risiko Mahasiswa terhadap Penggunaan Kecerdasan Buatan (AI) dalam Kreativitas dan Inovasi Pembelajaran - Pranoto Effendi (Pusat Riset dan Inovasi Nasional, 2024)
The use of AI is seen as aiding the learning process, and students have used AI for various purposes in their coursework. This article aims to investigate the impact of AI use on their innovation and creativity, as well as the possibility of AI replacing lecturers. A qualitative study was conducted with 53 student respondents. Questions were asked about the definition of AI, the applications of AI they use, whether AI can enhance creativity and innovation, and whether AI will one day replace lecturers. The findings indicate that AI is artificial intelligence that serves as an aid in the student learning process. The majority of students use ChatGPT, and 37 students stated that AI can enhance their innovation and creativity by providing inspiration and initial ideas. AI is also a tool that accelerates the learning process and facilitates creative work, as well as AI as a means of developing skills such as critical reasoning and data analysis. However, the majority also stated that dependence on AI can actually reduce critical thinking and creativity. Regarding the role of lecturers, 41 students stated that AI cannot replace them. The implication of these findings is that AI can be used wisely while still being aware of its limitations and ethical use. The role of lecturers must be further enhanced to ensure that student learning processes address AI's limitations and allow students to further enhance their innovation and creativity, while simultaneously mitigating the associated risks.